Three essays on the relatioship between income inequality and aggregate demand - Sanches, Marina da Silva (2024)
This Doctorate Dissertation comprises three essays. Chapter 1 builds a neo-Kaleckian model to study the relationship between earnings inequality and fluctuations in aggregate demand. The model includes three classes in a Kaleckian-Goodwinian approach capitalists and two types of workers (production and professional). We build a relationship between earnings inequality and aggregate demand mediated by the employment rate in the medium run. We conclude that the stability of this relationship relies on the presence of a conciliation mechanism between the two categories of workers in a distributive conflict context. We also simulate some policy impacts. In particular, the paper highlights the importance of policies that increase the production workers share in income, as they have positive effects on both distributional and aggregate demand aspects, regardless of the demand regime. Chapter 2 and Chapter 3 contribute to the empirical literature on the impacts of fiscal austerity on inequality by analyzing the dynamic effects of fiscal consolidation episodes on disposable income, market income, wage, and functional inequalities. Using a Gini decomposition approach, the Chapters are the first empirical studies in the macroeconometric literature on the relationship between fiscal consolidation and inequality that identify the importance of the different transmission channels for this effect. While Chapter 2 uses the narrative dataset from Alesina et al. (2019) for a group of OECD countries from 1978 to 2014, Chapter 3 employs a narrative dataset covering 1989-2016, from David and Leigh (2018) for a group of countries from Latin America and the Caribbean. Using the methodology proposed by Jordà (2005), we derive impulse response functions from local projections. In Chapter 2, we find: i) the redistributive measure responds positively to fiscal austerity shocks in the short run, indicating the market income inequality increases more than the disposable income inequality. It shows the importance of automatic stabilizers and the social safety net; ii) both wage and functional channels exhibit similar statistically significant responses in the short run; iii) in the medium run, the redistributive effect is not statistically significant, and the functional inequality channel loses significance; iv) in the medium run, wage inequality emerges as the primary channel affecting income inequality; v) in short and medium runs, the impact on non-labor inequality might be equalizing; vi) the employment channel suggests that austerity measures increase earnings inequality, especially if we consider the lower end of earnings distribution; vii) spending-based shocks exhibit more relevant impacts on inequality. Our main results in Chapter 3 are: i) the redistributive measure responds positively to fiscal shocks in the short run, indicating the market income inequality increases more than the disposable income inequality; ii) the functional inequality channel displays the most relevant impact in the short run; iii) in the medium run, the redistributive effect decreases after tax-based fiscal episodes, suggesting the disposable income inequality responds more; iv) the wage inequality channel is the most relevant channel in the medium run; v) in both short and medium runs, the impact on non-labor inequality might be equalizing; vi) the impact of austerity on inequality is more pronounced during low economic growth periods and when the size of the fiscal package is large; vii) spending-based shocks exhibit more relevant impacts on inequality.